Against the tide: the commencement of short selling and margin trading in mainland China. (27th June 2013) - Sharif, Saqib; Anderson, Hamish D.; Marshall, Ben R.; Berkman, Henk
Abstract China's recent removal of short‐selling and margin trading bans on selected stocks enables testing of the relative effect of margin trading and short selling. We find the prices of the shortable stocks decrease, on average, relative to peer A‐shares and cross‐listed H‐shares, suggesting that short selling dominates margin trading effects. Contrary to the regulators' intention and recent developed market empirical evidence, liquidity declines and bid‐ask spreads increase in these shortable stocks. Consistent with Ausubel (1990), these results imply that uninformed investors avoid the shortable stocks to reduce the risk of trading with informed investors.